Differential expression of THELPER1 cytokines upon antigen stimulation predicts ex vivo proliferative potential and cytokine production of virus‐specific T cells following re‐stimulation. Issue 5 (9th September 2014) - Feucht, J.; Leibold, J.; Halder, A.; Kayser, S.; Hartl, L.; Rammensee, H.‐G.; Handgretinger, R.; Feuchtinger, T.
Abstract Introduction Cytomegalovirus (CMV) and human adenovirus (ADV) infections are causes of morbidity after stem cell transplantation. Antigen (Ag)‐specific T cells are essential for the control of viral infections. However, in vivo expansion potential of T‐cell subpopulations is hardly predictable in humans. Furthermore, ex vivo identification of human T cells with repopulating capacity for adoptive T‐cell transfer has been difficult. Methods We analyzed Ag‐specific T‐cell populations, subdivided according to the expression of different THELPER‐1 (Th1) cytokines. Isolation by flow cytometry was based on interferon‐gamma (IFN)‐γ, interleukin (IL)‐2, or tumor necrosis factor‐alpha (TNF‐α) secretion of T cells after ex vivo stimulation with the Ags hexon (for ADV) and pp65 (for CMV). Isolated T cells were expanded and examined for functional characteristics, expansion/differentiation potential, and naïve, effector memory, central memory, and late effector phenotypes. Results Isolation based on IFN‐γ production provides a T‐cell population with a mixture of early, central memory, and effector memory T cells, high expansion potential, and effective cytokine production. Selection of T cells with Ag‐specific expression of IL‐2 or TNF‐α, however, results in a T‐cell population with reduced proliferation and lower effector potential after expansion. Conclusion We conclude that the exclusive secretion of IFN‐γ in the human antiviral T‐cell responses preferentially leads to higher repopulation capacities of antiviral T cells, compared to IL‐2 or TNF‐α secreting T‐cell populations.